Pengendalian Risiko dengan Pendekatan Socio-technical Risk Management pada Supply Bahan Baku Pallet Kayu - Issa Dyah Utami; Ahmad Mughni; Dian Rachma Anggraini (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2018)
Pallet Industries have an important role in supporting the smooth supply chain activities. Research on risk control in the pallet industry's inbound logistics is still not widely implemented. The risk caused by activities and process of raw materials procurement in the wood pallet industry is a crucial problem that must be immediately assisted to find a model solution. This study presents a new model in risk management by applying a socio-technical system approach to identifying, evaluating, and determining risk control strategies. A case study on an wood pallet industry in East Java was presented to validate the risk management model. Results of the risk assessment show that the highest risk was loss of raw material (R23). This risk was included in the safety perspective, so transferring risk to an insurance company was recommended to mitigate the risk. The results of this study were expected to help the pallet industry in minimizing losses due to risks in the inbound logistic process.